The Effectiveness of the Coal Mining Licensing System in the Implementation of Sustainable Development Goals - Arrie Budhiartie; Ridha Aulia Zarifah; Deco Anderson Valentino; Diva Puspita Aprilia; Zahra Deffiana; Yusupha Jabbi (PATTIMURA Legal Journal, 2025)
Introduction: The mining licensing system is a key instrument in controlling coal exploitation activities to achieve sustainable development targets after the adoption of the 2015 Sustainable Development Goals (SDGs). However, there are problems in the licensing function as an environmental impact control mechanism and disparities between national regulations and policy implementation at the regional level that hinder the achievement of sustainable mining goals. Purposes of the Research: The purpose of writing this article is to evaluate the effectiveness of the coal sector licensing mechanism in Jambi City in adopting SDGs values and examine the challenges of implementing sustainable mining policies at the local level. Methods of the Research: The research uses a qualitative approach with a descriptive analysis method on the mining licensing system in Jambi City. Data collection techniques through documentation studies on regional licensing policies, Mayor's regulations in the field of mining, regulations on coal sector control, and analysis of literature from relevant scientific sources. Results Main Findings of the Research: The research reveals that the coal licensing system in Jambi City has adopted the principles of SDGs 12 (responsible consumption and production) through the Decree of the Mayor of Jambi Number 54 of 2023 concerning the control of coal transportation, the optimization of the licensing function as an environmentally friendly production control tool, and the establishment of a multi-agency coordination system in the supervision of responsible production practices, However, there are still weaknesses in the implementation of sanctions and the synchronization of central and regional policies.